PRESIDENTIAL ELECTION 2024: ENSURING COMPLIANCE AND ACCOUNTABILITY THROUGH CRIMINAL LAW ENFORCEMENT IN ELECTRONIC ELECTIONS - Pirmansyah, Redi; Junaidi; Merta, Martino (Awang Long Law Review, 2025)
The integration of digital technology into electoral processes marks a significant transformation in modern democracies, including Indonesia. Electronic-based elections have been implemented to improve the efficiency, transparency, and accessibility of the electoral process. However, this shift has also introduced a range of challenges, such as cybercrime, data leaks, misinformation, and legal ambiguities. The 2024 Presidential Election presents a critical opportunity to evaluate the effectiveness of criminal law enforcement in safeguarding the integrity of electronic elections. This research aims to assess how Indonesia’s legal system ensures compliance and accountability in the context of electronic voting. Utilizing a normative juridical approach, the study draws on primary legal materials specifically Law Number 7 of 2017 concerning General Elections and analyzes legal theories, principles, and doctrines relevant to electoral and criminal law. The findings reveal a regulatory gap in the current legal framework, where specific provisions addressing electronic electoral crimes are lacking. Consequently, enforcement efforts rely heavily on general laws such as the Electronic Information and Transactions Law, which are insufficient for addressing the complexity of digital election violations. The study emphasizes the urgent need to revise the Election Law to include detailed criminal provisions related to electronic election offenses, including classifications of violations, enforcement mechanisms, and accountability measures. In addition, the research highlights the positive impact of digital monitoring tools like Siwaslu and Gowaslu, implemented by Bawaslu, in enhancing election. Strengthening these legal and institutional aspects is essential to ensure that the 2024 Presidential Election upholds democratic principles in an increasingly digital landscape.